2009
DOI: 10.1161/hypertensionaha.108.123612
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Activation of Renin-Angiotensin System Impairs Cognitive Function in Renin/Angiotensinogen Transgenic Mice

Abstract: Abstract-We examined the possibility that continuous activation of the human brain renin-angiotensin system causes cognitive impairment, using human renin (hRN) and human angiotensinogen (hANG) gene chimeric transgenic (Tg) mice. Cognitive function was evaluated by the shuttle avoidance test once a week from 10 to 20 weeks of age. The avoidance rate in wild-type mice gradually increased. In contrast, the avoidance rate in chimeric hRN/hANG-Tg mice also increased; however, no further increase in avoidance rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 43 publications
5
68
0
3
Order By: Relevance
“…We recently showed that HFD induced changes in the expression of several genes in mice brain (12). On the other hand, recent papers reported that transgenic mice expressing human RENIN and AGT genes (hRN/hAGT-Tg) have impaired cognition, increased oxidative stress, and ischemic damage in the brain mediated by overstimulation of AT1R (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that HFD induced changes in the expression of several genes in mice brain (12). On the other hand, recent papers reported that transgenic mice expressing human RENIN and AGT genes (hRN/hAGT-Tg) have impaired cognition, increased oxidative stress, and ischemic damage in the brain mediated by overstimulation of AT1R (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that AT 1 receptor blockers reduce oxidative stress in the brain, as well as in the peripheral vasculature. It is also possible that AT 1 receptor blockers inhibit ROS production by blocking AT1 receptormediated intracellular signaling (11,48,50) and that this antioxidant action accounts for the absence of reflex-induced sympathoexcitation after treatment with AT 1 receptor blockers. We evaluated the effects of AT 1 receptor blockers, olmesartan and telmisartan, on brain oxidative stress in SHRSP (4,48).…”
Section: Sympathoinhibitory Effects Of Antihypertensive Drugs and Stamentioning
confidence: 99%
“…6 PREVENTION OF METABOLIC SYNDROME-INDUCED DEMENTIA Continuous activation of the brain RAS impairs cognitive function through stimulation of the AT 1 receptor. 23 The ARB candesartan ameliorates impaired cognitive function in mice with type 2 diabetes (KKAy), at least partly, because of increased expression of MMS2 and an improvement in glucose intolerance. 24 Interestingly, another ARB, olmesartan, is therapeutically effective at preventing the impairment of cognition in mice fed a high-fat and high-salt diet.…”
Section: Enhancement Of Neural Differentiationmentioning
confidence: 99%